Pengembangan Strategi Pembelajaran dalam Perspektif Pendidikan Islam - Moh. Roqib (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Educator obliged to have skill to develop learning strategy that enjoyable (edutainment) so that student motivated to learn continuously. In that happy situation, educator can apply active and creative learning strategy to shape good character. This effort has made Islamic education developed and attracts people’s interest for its quality. Islamic educator and institution as madrasah and PTAI (Perguruan Tinggi Agama Islam—higher Islamic college) known as education plus because combine science and religion with trusted quality. Therefore, some important key concepts are method, strategy, and learning technique that have dynamic character and based on Islam’s perspective.